PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PLATFORM GENIALLY PADA MATERI TEKS DESKRIPSI SISWA KELAS VII SMP - Rina Marianti; Silvia Permatasari; Zulhafizh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the validity level of interactive learning media based on the Genially platform for descriptive text material for seventh-grade junior high school students. The research method used is Research and Development (R&D) with the ADDIE model. After the development process, the learning media was validated by three validators: a material expert, a media expert, and a language expert. The research instrument used was a validation sheet, which was then analyzed to obtain a validation score. Based on the data analysis results, the interactive learning media based on the Genially platform was declared valid with an average validation percentage of 91%, thus categorized as highly valid. Therefore, the Genially-based learning media for teaching descriptive texts is considered suitable for use in the teaching and learning process by both students and teachers.